A REVIEW ON ETHNOMEDICINAL AND TRADITIONAL USES OF ELAEOCARPUS GANITRUS ROXB. (RUDRAKSHA) - SURESH C. JOSHI; PRATIBHA K. JAIN (International Journal of Pharma and Bio Sciences, 2014)
In the present review, an attempt has been made to congregate the botanical, phytochemical, ethno medicinal, pharmacological information on Elaeocarpus ganitrus Roxb. belongs to family Elaeocarpaceae. It is prevalent for its fascinating fruit stones and medicinal properties. It procures a remarkable position in Hinduism and Ayurveda, the indigenous system of medicine. In Hindi it is recognized as Rudraksha, is a large evergreen broad-leaved tree whose seed is conventionally used for prayer beads in Hindu religion. In traditional system of medicine, different parts (beads, bark, leaves and outer shell of beads) of Rudraksha are taken for the alleviation of various health problems such as mental disorders, headache, fever, skin diseases, and for healing the wounds. Ayurvedic texts categorise Rudraksha fruits as thermogenic, sedative, cough alleviator and are useful for the treatment of bronchitis, neuralgia, cephalagia, anorexia, migraine, manic conditions and other brain disorders. It is employed in folk medicine as a counter agent of stress, anxiety, depression, palpitation, nerve pain, epilepsy, lack of concentration, asthma, hypertension, arthritis and liver diseases. Furthermore it is retrieve to exhibit multifarious pharmacological activities like anti-inflammatory, analgesic, hypoglycemic, antiulcerogenic and very high antimicrobial activity. Phytosterols, fats, alkaloids, flavonoids, carbohydrates, proteins and tannins have been found to be largely responsible for the therapeutic potential of E. ganitrus. Aqueous extract of leaves contains glycosides also. Ethanolic extract of leaves contains gallic acid, ellagic acid & quercetin. This review provides a scientific basis for pharmacological /medicinal properties and therapeutic uses of Elaeocarpus ganitrus Roxb.